PENETAPAN KADAR SENYAWA ABBRASIYE (CALSIUM) PADA PASTA GIGI - Ana Hidayati M; Edy Setyorini (JURNAL LITBANG, 2005)
Abstract The quantitative determination of abrasive concentration (Calcium) on toothpaste has been studied. The research purposed to certain abrasive concentration (Calcium) of toothpaste and what abrasive concentration (Calcium) of toothpaste was Harry's Cosmeticologt Standard. Formulation of toothpastes are abrasive, gelling agent, humectants, sweetener, surface active, agent, color preservative, prophylactic agent, and water Abrasive concentration (Calcium) on tooth paste prohibited chocolate layer on tooth and over abrasive prohibited abrasive surface on tooth. The Complexometry method is used to determined abrasive concentration (Calcium) on toothpaste. The abrasive concentration (Calcium) on toothpaste by Harry's Cosmeticologt Standard was 15 50 % b/b. The analysis is performed complexion by addition Na OH I N pH12 in the sample solution and murex idée indicator and titrated with Standard solution of Na2EDTA to red-violet colour The research results that abrasive concentration (Calcium) on four mark of Tooth pastes A, B, C, and D codes in a series are 45,92 % b/b, 47,380% b/b, 47,599 % b/b, and 45,99 % b/b, and witch re canceled by Harry's Cosmeticologt Standard was 15 5 0 % b/b. KeyWords : Abrasive concentration, Calcium, Tooth paste, Standard Harry's Cosmeticologt